Pendekatan Komunikasi Interpersonal Orang Tua Dalam Membimbing Anak Belajar Daring Di Masa Pandemi Covid-19 - Nurfarida Deliani; Dr Kunalan Kuriaya; Syawaluddin Syawaluddin; Masrial Masrial; Abd Rahman; Jemkhairil JemKhairil; Ahmad Putra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The purpose of this study is to see how parents do daily interpersonal communication in guiding their children to learn online during the COVID-19 pandemic in Karang Tangah Pesisir Selatan Village. As long as learning is done online, parents feel the maximum in guiding their children to learn online, but in reality this is not the case. With the various responses that children see when learning online, parents try to guide their children in various ways and methods. This research is a field research using a qualitative method with a descriptive approach. Data was collected by means of observation and interviews. The subjects in this study were 3 parents who were determined by purposive sampling technique. The results of this study indicate that: First, in an informative approach, parents carry out interpersonal communication in guiding children to learn online related to online learning tasks given by the teacher every day through the whatsapp group. Second, parents have done it gently in a persuasive approach in guiding children to learn online. Third, at the stage of the instructive approach, parents try not to do anything that contains elements of coercion and violence against children or something that is threatening, punishing and physically taking because they don't want children to feel forced and burdened in online learning.